mtDNA heteroplasmy level and copy number indicate disease burden in m.3243A>G mitochondrial disease - John P Grady; Sarah J Pickett; Yi Shiau Ng; Charlotte L Alston; Emma L Blakely; Steven A Hardy; Catherine L Feeney; Alexandra A Bright; Andrew M Schaefer; Gráinne S Gorman; Richard JQ McNally; Robert W Taylor; et al. (EMBO Molecular Medicine)
Abstract Mitochondrial disease associated with the pathogenic m.3243A>G variant is a common, clinically heterogeneous, neurogenetic disorder. Using multiple linear regression and linear mixed modelling, we evaluated which commonly assayed tissue (blood N = 231, urine N = 235, skeletal muscle N = 77) represents the m.3243A>G mutation load and mitochondrial DNA (mtDNA) copy number most strongly associated with disease burden and progression. m.3243A>G levels are correlated in blood, muscle and urine (R2 = 0.61–0.73). Blood heteroplasmy declines by ~2.3%/year; we have extended previously published methodology to adjust for age. In urine, males have higher mtDNA copy number and ~20% higher m.3243A>G mutation load; we present formulas to adjust for this. Blood is the most highly correlated mutation measure for disease burden and progression in m.3243A>G‐harbouring individuals; increasing age and heteroplasmy contribute (R2 = 0.27, P < 0.001). In muscle, heteroplasmy, age and mtDNA copy number explain a higher proportion of variability in disease burden (R2 = 0.40, P < 0.001), although activity level and disease severity are likely to affect copy number. Whilst our data indicate that age‐corrected blood m.3243A>G heteroplasmy is the most convenient and reliable measure for routine clinical assessment, additional factors such as mtDNA copy number may also influence disease severity.